COMMUNITY SERVICE IMPOSED UPON THE CONVICTED CORRUPTOR IN ACTUALIZING LOCAL WISDOM AS CULTURAL HERITAGE - Dewi Asri Yustia; Gialdah Tapiansari; Tia Ludiana (SAMPURASUN, 2021)
Optimizing social work crime for convicted corruption is interpreted as an effort to provide positive value to the community in addition to reducing the burden on the state, both the burden of costs incurred by the state in fostering convicts and the burden of coaching, because the convicted person has more specific competencies both in the scientific field, authority as well as in other fields compared to the competency of the guiding apparatus without intending to play down the capabilities of the coaching apparatus, besides the security burden that must be carried out by the state, because given the provision of criminal work, the obligation to carry out criminal offenses is transferred to convicts not to the state , and the benefits felt not only for the country but also for the people ,because the competency of the perpetrators can be useful, and it becomes a legal effort in actualizing local wisdom, because the sanctions applied are more concentrated on the needs of the community and community-based coaching, and prison is no longer the only coaching institution for perpetrators of corruption, so It is expected that the recommendations for the renewal of the Criminal Code and the Corruption Law can achieve the goal of punishment, namely providing deterrence for perpetrators and also providing positive benefits for the community while reducing the burden on the state.